Outdoor thermal comfort of shaded spaces in an urban park in the cold region of China. (15th May 2019) - Xu, Min; Hong, Bo; Jiang, Runsheng; An, Le; Zhang, Ting
Abstract: This study aims to identify outdoor thermal benchmarks of shaded spaces in an urban park in Xi'an (China). Meteorological measurements were conducted during winter and summer accompanied by a subjective thermal sensation questionnaire. The Universal Thermal Climate Index (UTCI) was applied to quantitatively analyze the thermal comfort range in Xi'an, and then variations in outdoor thermal benchmarks between Xi'an and other climatic zones were compared. Results demonstrated that: (1) Air temperature and globe temperature were the dominant physical factors affecting outdoor thermal comfort (OTC) in Xi'an. (2) Pavilion shade effectively lowered thermal stress, decreasing UTCI by 15.5 and 10.1 °C during winter and summer. (3) Deciduous tree shade was the optimal shading design measure and could meet demands for thermally comfortable environments. (4) The neutral UTCI in Xi'an was found to be 23.1 °C, and the acceptable UTCI ranged from 18.0 to 29.1 °C, and (5) a thermal comfort calendar for shaded spaces demonstrated that "strong cold stress" or higher occurred after 16:00h in winter. Pavilion and deciduous tree shades were "neutral thermal stress" for 24h in summer. The results identify thermal benchmarks that could help urban designers create thermally comfortable outdoor spaces in urban parks within the cold region of China. Highlights: Thermal comfort conditions of shaded spaces in Xi'an, China were investigated. T a and T g were the dominant physical factors affecting OTC in Xi'an. UTCI satisfactorily predicted OTC with neutral value of 23.1 °C. The range of acceptable neutral UTCI stretched from 18.0 °C to 29.1 °C. A thermal comfort calendar was proposed for leisure and recreational activities.